Neural Representations of the Full Spatial Field in Auditory Cortex of Awake Marmoset (Callithrix jacchus) - Remington, Evan D; Wang, Xiaoqin (Cerebral cortex (New York, N.Y. 1991), 2019)
Abstract Unlike visual signals, sound can reach the ears from any direction, and the ability to localize sounds from all directions is essential for survival in a natural environment. Previous studies have largely focused on the space in front of a subject that is also covered by vision and were often limited to measuring spatial tuning along the horizontal (azimuth) plane. As a result, we know relatively little about how the auditory cortex responds to sounds coming from spatial locations outside the frontal space where visual information is unavailable. By mapping single-neuron responses to the full spatial field in awake marmoset (Callithrix jacchus), an arboreal animal for which spatial processing is vital in its natural habitat, we show that spatial receptive fields in several auditory areas cover all spatial locations. Several complementary measures of spatial tuning showed that neurons were tuned to both frontal space and rear space (outside the coverage of vision), as well as the space above and below the horizontal plane. Together, these findings provide valuable new insights into the representation of all spatial locations by primate auditory cortex.